Urban Housing Markets : Recent Directions in Research and Policy - Bourne, Larry, S. (Book collections on Project MUSE., 1978)
This volume is both a record of the Conference on Urban Housing Markets sponsored by the Centre for Urban and Community Studies in October 1977 and a review of important recent research on urban housing markets and related public policy issues.